PROSES BERPIKIR REFLEKTIF SISWA KELAS VII SMP NEGERI 3 POLANHARJO KLATEN DALAM PEMECAHAN MASALAH PECAHAN - Wahyuni, Fina Tri; Sujadi, Imam; Subanti, Sri (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aims of this research was to describe the characteristics of reflective thinking process of the students in Grade VII of State Junior Secondary School 3 ofÂ  Polanharjo Klaten who have the high, moderate, and low abilities in solving fractional problems. This research used qualitative case study approach. The data of research were gathered through task-based in-depth interview. The results of research were the characteristics of reflective thinking process of the students as follows: 1) The students with the high initial ability in Mathematics: (a) in the problem understanding phase, they were able to mention information of the problems and to explain what has been done; (b) in the problem-solving planning phase, they were able to identify the concept of the problems and to explain what has been done; (c) in the implementation of problem-solving plan phase, they were able to realize the mistakes and to fix them, to examine the truth of an argument, to employ the internal knowledge, to relate the information that they have known, and to communicate ideas with symbols instead of pictures or direct objects; and (d) in the reexamination phase, they were able to draw conclusions to return the answers back into the contexts and to explain what has been done. 2) The students with the moderate initial ability in Mathematics: (a) in the problem understanding phase, they were able to mention information of the problems and to explain what has been done; (b) in the problem-solving planning phase, they were able to identify the concept of the problems, to employ the internal knowledge, to relate the information that they have known, and to explain what has been done; (c) in the implementation of problem-solving plan phase, they were unable to do reflective thinking; (d) in the reexamination phase, they were able to draw conclusions to return the answers back into the contexts and to explain what has been done. 3) The students with the low initial ability in Mathematics were able to do reflective thinking merely on the problem understanding phase, with the following characteristics: they were able to mention information of the problems and to explain what has been done.Keywords: Characteristics of reflective thinking process, problem solving, and initial ability in Mathematics.